Kinetics of ventilation-induced changes in diaphragmatic metabolism by bilateral phrenic pacing in a piglet model - Breuer, T.; Hatam, N.; Grabiger, B.; Marx, G.; Behnke, Bradley J.; Weis, J.; Kopp, R.; Gayan-Ramirez, G.; Zoremba, N.; Bruells, C. S. (My University, 2017)
Perioperative necessity of deep sedation is inevitably associated with diaphragmatic inactivation. This study investigated 1) the feasibility of a new phrenic nerve stimulation method allowing early diaphragmatic activation even in deep sedation and, 2) metabolic changes within the diaphragm during mechanical ventilation compared to artificial activity. 12 piglets were separated into 2 groups. One group was mechanically ventilated for 12 hrs (CMV) and in the second group both phrenic nerves were stimulated via pacer wires inserted near the phrenic nerves to mimic spontaneous breathing (STIM). Lactate, pyruvate and glucose levels were measured continuously using microdialysis. Oxygen delivery and blood gases were measured during both conditions. Diaphragmatic stimulation generated sufficient tidal volumes in all STIM animals. Diaphragm lactate release increased in CMV transiently whereas in STIM lactate dropped during this same time point (2.6 vs. 0.9 mmol L-1 after 5:20 hrs; p < 0.001). CMV increased diaphragmatic pyruvate (40 vs. 146 mu mol L-1 after 5:20 hrs between CMV and STIM; p < 0.0001), but not the lactate/pyruvate ratio. Diaphragmatic stimulation via regular electrodes is feasible to generate sufficient ventilation, even in deep sedation. Mechanical ventilation alters the metabolic state of the diaphragm, which might be one pathophysiologic origin of ventilator-induced diaphragmatic dysfunction. Occurrence of hypoxia was unlikely.
Citation: Breuer, T., Hatam, N., Grabiger, B., Marx, G., Behnke, B. J., Weis, J., . . . Bruells, C. S. (2016). Kinetics of ventilation-induced changes in diaphragmatic metabolism by bilateral phrenic pacing in a piglet model. Scientific Reports, 6, 10. doi:10.1038/srep35725
Keywords: Targeted Antioxidants Protect; Mechanical Ventilation; Rat Diaphragm; Cardiothoracic Surgery; Nerve Stimulation; Oxidative Stress